High-performance bioelectrocatalysts created by immobilization of an enzyme into carbon-coated composite membranes with nano-tailored structures. Issue 38 (15th September 2017) - Itoh, Tetsuji; Shibuya, Yuuta; Yamaguchi, Akira; Hoshikawa, Yasuto; Tanaike, Osamu; Tsunoda, Tatsuo; Hanaoka, Taka-aki; Hamakawa, Satoshi; Mizukami, Fujio; Hayashi, Akari; Kyotani, Takashi; Stucky, Galen D.
Abstract : We have achieved direct electron transfer between enzymes and electrodes through establishment of a regular enzyme array by encapsulation it in a carbon-coated composite membrane with mesoporous silica nanotubes (C/F127MST). Abstract : A large (40 mm ϕ ) composite membrane with mesoporous silica nanotubes (F127MST) was coated with a thin carbon layer (1–2 graphene sheets) by carrying out chemical vapor deposition (CVD) using acetylene, and the obtained carbon-coated F127MST (C/F127MST) was used directly as an electrode. After evaluating the electrical conductivity inside the continuous mesopore network, the enzyme bilirubin oxidase (BOD) was loaded into the mesopores of C/F127MST to form BOD–C/F127MST. Indeed, this loading procedure was effective and achieved direct electron transfer between the enzymes and electrodes. The loading also was found to enhance the stability of stored BOD (it was stable for 15 days) and could be used to control the enzymatic reaction by varying the electric potential. We therefore consider BOD–C/F127MST to be a promising candidate as an effective bioelectrode in various fields.